Increased Competition in an Unfavourable Audit Market Following Audit Privatisation: The Iranian Experience - Mohammad Rezaei, Fakhroddin; Mohd Saleh, Norman; Ali, Muhammad Jahangir (Asian Journal of Business and Accounting, 2015)
A sudden surge of competition following audit privatisation in the Iranian audit market may create some positive or negative consequences on audit quality. Such significant accounting reform occurred in the unfavourable audit market of Iran where the demand for high quality audit services as well as litigation risks are low. This study examines whether increased competition in the Iranian audit market has any impact on audit fees, audit quality and auditor switching. Findings from this study indicate that increased competition in an unfavourable audit market is more likely to result in unfavourable consequences encompassing price competition (decreasing audit fees) rather than quality competition (audit quality improvement), and increased opportunistic auditor switching. This study offers policymakers some suggestions to mitigate the potentially unfavourable consequences of increased competition in an unfavourable audit market. Keywords: Audit Fees, Audit Market Competition, Audit Privatisation, Audit Quality, Auditor Switching, Iran, Unfavourable Audit Market JEL Classification: M42